Diaquabis{2-[5-(2-pyridyl)-2H-tetrazol-2-yl]acetato-κ2N4,N5}zinc(II) - Bo Wang (Acta Crystallographica Section E, 2009)
The title compound, [Zn(C8H6N5O2)2(H2O)2], was synthesized by hydrothermal reaction of ZnBr2 with 2-[5-(2-pyridyl)-2H-tetrazol-2-yl]acetic acid. The ZnII atom lies on an inversion center in a distorted octahedral environment with two planar trans-related N,N′-chelating 2-[5-(2-pyridyl)-2H-tetrazol-2-yl]acetic acid ligands in the equatorial plane and two water molecules in the axial positions. In the crystal, O—H...O hydrogen bonds generate an infinite three-dimensional network.